2015
DOI: 10.3109/14767058.2015.1016422
|View full text |Cite
|
Sign up to set email alerts
|

Decreased hazard of necrotizing enterocolitis in preterm neonates receiving red cell transfusions

Abstract: RBCT exposure was associated with decreased hazards for NEC in preterm infants in this study; factors previously reported to be associated with NEC remained statistically significant predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 51 publications
2
31
0
1
Order By: Relevance
“…Early, retrospective studies evaluating the administration of red blood cell (RBC) transfusion in neonates demonstrated an increased risk of NEC after RBC transfusion, 58 while more recent studies have reported no association 9, 10 or even protection from NEC after receipt of RBC transfusion. 11, 12 A recent secondary, prospective analysis performed by Patel et al concluded that severe anemia, rather than RBC transfusion, was actually the factor associated with an increased risk of NEC. 13 Though the relationship between NEC and blood transfusion has been extensively studied, there has been no definitive evidence that blood transfusion is a causative risk factor for the development of NEC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early, retrospective studies evaluating the administration of red blood cell (RBC) transfusion in neonates demonstrated an increased risk of NEC after RBC transfusion, 58 while more recent studies have reported no association 9, 10 or even protection from NEC after receipt of RBC transfusion. 11, 12 A recent secondary, prospective analysis performed by Patel et al concluded that severe anemia, rather than RBC transfusion, was actually the factor associated with an increased risk of NEC. 13 Though the relationship between NEC and blood transfusion has been extensively studied, there has been no definitive evidence that blood transfusion is a causative risk factor for the development of NEC.…”
Section: Introductionmentioning
confidence: 99%
“…6, 10, 12, 1416 A better understanding of the relationship between RBC transfusion and the development of NEC is critical since more than 50% of VLBW infants (<1500g) receive RBC transfusions. 17 We sought to investigate the relationship between RBC transfusion and NEC at our institution, and the objective of this study was to determine if RBC transfusion in premature infants was associated with worse outcomes related to NEC.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, more recent observational studies have found no association between RBC transfusion and NEC 5,6 or have found RBC transfusion to be protective. 7,8 In addition, a meta-analysis of randomized trials reported no difference in the incidence of NEC between infants receiving conservative vs liberal RBC transfusion approaches (pooled odds ratio, 1.67 [95% random-effects CI, 0.82-3.38]). 9 …”
mentioning
confidence: 99%
“…Because many of our infants required vasopressors, there is increased likelihood they also required transfusions. However, several recent studies have suggested an absence of increased NEC risk with transfusions [49,50]. The lack of caffeine TDM in our patient population may also be a limitation; however, the measurement of serum caffeine concentrations has not been shown to correlate with clinical efficacy or toxicity [40].…”
Section: Discussionmentioning
confidence: 86%